Characterization of Mango-ginger (Curcuma amada Roxb.) Germplasms Through Isozyme Analysis (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Mango-ginger, isozyme, characterizationBangladesh j. genet. biotechnol. 7(1&2): 5-9 2006 (June & December)